2021
DOI: 10.3390/molecules26175301
|View full text |Cite
|
Sign up to set email alerts
|

Short Overview of Some Assays for the Measurement of Antioxidant Activity of Natural Products and Their Relevance in Dermatology

Abstract: Impaired systemic redox homeostasis is implicated in the onset and development of various diseases, including skin diseases. Therefore, continuous search for natural products with antioxidant bioactivities applicable in biomedicine is attractive topic of general interest. Research efforts aiming to validate antioxidant potentials of natural products has led to the development of several assays based on various test principles. Hence, understanding the advantages and limitations of various assays is important f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 119 publications
0
5
0
Order By: Relevance
“…Natural products with antioxidant activity have been recognized as valuable tools in the management of oxidative/nitrosative stress-induced pathologies [19]. Plants that contain certain amounts of polyphenols and flavonoids are perfect sources of antioxidants [20,21], but some studies infirmed this claim [22].…”
Section: Pharmacological Studies 221 Total Antioxidant Capacitymentioning
confidence: 99%
“…Natural products with antioxidant activity have been recognized as valuable tools in the management of oxidative/nitrosative stress-induced pathologies [19]. Plants that contain certain amounts of polyphenols and flavonoids are perfect sources of antioxidants [20,21], but some studies infirmed this claim [22].…”
Section: Pharmacological Studies 221 Total Antioxidant Capacitymentioning
confidence: 99%
“…The main focus of the studies is on products prepared from plant extracts [10], essential oils [11], and microorganisms [12]. In this context, many different tests include the ferric reducing‐antioxidant power (FRAP) assay, the trolox equivalent antioxidant capacity (TEAC), the 2,3‐diphenyl‐1‐picrylhydrazyl (DPPH) free radical technique, and the total phenolic assay are performed to determine the antioxidant potency of products extracted from these natural sources [13, 14].…”
Section: Introductionmentioning
confidence: 99%
“…It is reported that natural plant products can scavenge free radicals that result in cell death, histological damage, and chronic conditions development [ 25 ]. Hesperetin has antioxidant activity.…”
Section: Resultsmentioning
confidence: 99%